(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
Osteochondral defects arising from trauma or degenerative changes in osteoarthritis present significant treatment challenges. Current therapies often fail to fully restore the complex, hierarchical structure of native joint tissue. To address these limitations, repair of osteochondral defects using scaffolds tissue engineering has shifted toward multiphasic and gradient designs [1]. Gradient designs are characterized in particular by providing a smoother transition between bone and cartilage, distributing the forces more efficiently across the scaffold and avoiding instabilities in the interface, making it less prone to interface delamination [2]. In this study, we 3D-printed gradient scaffolds featuring a polycaprolactone (PCL) subchondral bone phase and a cartilage phase composed of alginate-dialdehyde-gelatin (ADA-GEL) and ADA-GEL enriched with hyaluronic acid. We comprehensively characterized the mechanical properties of the gradient interface, including shear resistance, tensile strength, and dynamic responses under shear and compressive loads. In an in-vitro co-culture of human mesenchymal stem cells (hMSCs) in the subchondral part and primary human chondrocytes in the cartilage part, we assessed the osteogenic and chondrogenic performance of the gradient osteochondral scaffolds.